Challenges and Opportunities of the 2022 G20 Summit in Strengthening Prevention, Preparedness, and Response (PPR) Financing as a Part of Global Health Architecture Restructuration - Kevin Abimanyu Jatmiko (Global South Review, 2022)
Restructuring and strengthening the framework of Global Health Architecture (GHA) is one of the significant agendas raised at the 2022 G20 Summit held in Bali, Indonesia. One of the identified motivations behind this initiative concerns the gap in the prevention, preparedness, and response (PPR) financing policy and its sustainability. This problem generates inequity in the global health system–especially experienced by the low- and mid-income countries (LMICs)–and hinders the effort to comprehensively mitigate the impacts the threats have caused, such as from the current COVID-19 outbreak. Consequently, these countries are struggling due to their inability to acquire healthcare resources such as health infrastructures, vaccine access, and human resources. To understand how the 2022 G20 forum could contribute to restructuring and strengthening the architecture, this paper investigates the upcoming summit's potential challenges and opportunities in restructuring the GHA framework to close the gap in financing PPR and creating an equal global health system. In doing so, this article will apply desk study by collecting information from secondary data sources. One of the potential opportunities is to strengthen global health multilateralism through the G20 members' active engagement in the financial intermediary fund (FIF) platform. However, there is also a significant challenge regarding the current global solidarity and political tension. Therefore, the forum must consider these notions to create a more robust and sustained financial policy to strengthen the architecture.